(3dPI GdSeY aj GdoeOGe hGdSeYs
(3ChdgG (B:s
(3Mci GdeZQe GdYGTb Yf GdeMH GdUGOb Cfg bGd(B: (3efP fTCoJ TQjO Gdcda HGdQGM, RGFO GdTZa HGdedGM s
(3BNQgG (B:s
(3hGKbkG HCf JYhO, hJhLgJ aj MQR GdSdGeI, hgG gfG NGJeI GdebGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B195 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B((3O (B1042) s
Keywords: (3GdCOHs